2020
DOI: 10.3390/ijerph17031087
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Profiles According to Their Beliefs and Affinity to Sexting. A Cluster Study

Abstract: Sexting consists of sending, receiving, and distributing images of sexually suggestive content through electronic devices. This practice is one of the new ways of linking sex affectively through virtual environments, especially in adolescence. However, not all young people have the same relationship with the practice of sexting. This study of a sample of 603 Spanish and Moroccan adolescents residing in Andalusia analyzes beliefs towards sexting as part of a virtual sexuality and the perception of those who car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
(47 reference statements)
0
2
0
1
Order By: Relevance
“…These young adolescents receive education and values influenced by the culture of their families in which they do not usually promote equality, but rather the opposite, submission towards males. The permanence of sexist values and traditional gender roles in these cultures reinforces discrimination and the assumption of the role of victim-survivor even in younger women [ 41 ]. In contrast, Spanish victim-survivors present different characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…These young adolescents receive education and values influenced by the culture of their families in which they do not usually promote equality, but rather the opposite, submission towards males. The permanence of sexist values and traditional gender roles in these cultures reinforces discrimination and the assumption of the role of victim-survivor even in younger women [ 41 ]. In contrast, Spanish victim-survivors present different characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Se han evidenciado similitudes entre los comportamientos online con las dinámicas sociales, de género y étnicoraciales (offline) preexistentes en la sociedad (Cava et al, 2015;Cava y Buelga, 2018;Fernández-Fuertes y Fuertes, 2010;Lorente, 2018;. Sin embargo, también se han descrito distintos guiones comportamentales sexuales, cultural sexual scripts, según si el escenario cultural es social (offline) o interactivo (online) (Simon y Gagnon, 1987;Soriano-Ayala et al 2020). La nueva cultura sexual virtual presenta características específicas como son el anonimato, las identidades virtuales, el distanciamiento, la exposición de la vida íntima y privada y la posibilidad de mayor control que favorecen el desarrollo de otras formas de ejercer ciberviolencia en la pareja (Estébanez, 2018;Lorente, 2018).…”
Section: Debates En Torno a La Ciberviolenciaunclassified
“…One of the most recent events that have caused changes in adolescents' relationships and behavior is the so-called "sexting", that is, the dissemination of erotic and sensual content through digital devices. Studies have shown that this practice is associated with unfavorable events such as cyberbullying, grooming, and sextortion [85][86][87] . The need for self-assertion and the attempt to gain confidence is often expressed in the appreciation of the number of likes that their posts receive with their social status, leading the teenager to create profiles that do not correspond to the reality to be accepted by colleagues [80,88] .…”
Section: Social Mediamentioning
confidence: 99%